Some uniqueness result on controllability for functional semilinear differential equations in Fréchet spaces - Arara, A.; Benchohra, M.; Ouahab, A. (Нелінійні коливання, 2003)
In this paper, a recent nonlinear alternative for contraction maps in Frechet spaces, due to Frigon and ´ Granas, is combined with semigroups theory and used to investigate the controllability of some classes of semilinear functional and neutral functional differential equations in Banach spaces on the semiinfinite interval.